"Non-strategic" Eastern Europe and the Fate of the Humanities. (February 2015) - Cavanagh, Clare
Until recent events intervened, Eastern European Studies found themselves under attack at my home university and other institutions for being, among other things, "non-strategic." We see the same notion, if not the same terminology, applied increasingly to the humanities and non-quantitative social sciences, which lose ground daily to the so-called STEM disciplines in both educational policy and practice. How do we defend the study of Eastern European literature and culture in the current academic climate? This essay defends the centrality both of literary and Eastern European studies in the twenty-first-century curriculum.